PENGEMBANGAN PENILAIAN PORTOFOLIO UNTUK MENILAI KEMAMPUAN BERPIKIR KREATIF SISWA KELAS IV SD NEGERI 2 BANJAR BALI KECAMATAN BULELENG TAHUN PELAJARAN 2018/2019 - Parwati Dewi Jatiningtyas (Guna Widya: Jurnal Pendidikan Hindu, 2019)
This research belongs to development reseach which aims to develop the portfolio instruments and their implementation to measure the students’ creative thinking skill in fourth grade students of SD Negeri 2 Banjar Bali Buleleng Subdistrinct in academic year 2018/2019. The reseach design which used in this study was Reseach and Development. This design was used ADDIE model namely; Analyze, Design, Development, Implementation, And Evaluation. There fourh instruments in collecting the data namely; obsevasion, quationnaire, portfolio, and documentation. The results of the study were analyzed by using quantitative descriptive analysis methods. The results of data analysis showed that the validity assessment of the instrument through validity test scored 32 by the first judgement with a very decent predicate, scored 27 by the second judgment with a very decent predicate, scored 27 by the third judgment with a very decent predicate, scored 32 by the fourth judgment with a very feasible predicate, and scored 32 by the fifth judgment with a very decent predicate. The instrument of portfolio assessment received a good responses and very good responses from its user. Based on the results, the instrument of development can be assumed that it can be used in learning process on the Tema 9 Kayanya Negeriku Subtema 3 Pelestarian Kekayaan Sumber Daya Alam in Indonesia